Effects of Surface Hydration and Application Method on the Bond Strength of Self-Etching Adhesives to Dentin - Gomes Torres, Carlos Rocha [UNESP]; Ferraz Caneppele, Taciana Marco [UNESP]; Borges, Alessandra Buhler [UNESP]; Shoji, Aline Vilanova; Nunes, Talita Macedo; Batista, Graziela Ribeiro [UNESP] (Taylor & Francis Ltd, 2011)
The effect of application methods and dentin hydration on the bond strength of three self-etching adhesives (SEA) were evaluated; 195 extracted bovine incisors were used. The buccal surface was ground in order to expose the dentin, which remained 2-mm minimum thickness, measured by a thickness meter through an opening on the lingual surface. Adper Single Bond 2 (TM) was used for the control group. The SEA were applied following two modes of application: passive or active and two hydration states of the dentin surface-dry and wet. After light-curing, composite buildups were made using Grandio (TM) composite. The specimens were sectioned and tested with a microtensile bond strength test. The application method and the hydration state resulted in statistical differences (p = 0.000) making the values of active application for mu TBS to dentin higher than passive application. The wet surfaces showed higher mu TBS to dentin ratios than dry surfaces. There were no statistical differences in mu TBS among the SEA tested but there were differences regarding to control group.
Keywords: Dentin; Microtensile bond strength; Self-etching adhesives